Ancient wisdom an introduction to sayings collections - Wilson, Walter T. 1962- (Chicago Wm. B. Eerdmans Publishing Co., 2022)
Intro -- Title Page -- Copyright -- Contents -- List of Abbreviations -- Introduction -- 1. ʾAbot -- 2. Ahiqar -- 3. Amenemope -- 4. Anii -- 5. Ankhsheshonqy -- 6. Ben Sira -- 7. Cato -- 8. Counsels of Wisdom -- 9. Democritus -- 10. Epictetus -- 11. Papyrus Insinger -- 12. Isocrates -- 13. Menander -- 14. Merikare -- 15. Pseudo-Phocylides -- 16. Porphyry -- 17. Proverbs -- 18. Ptahhotep -- 19. Publilius -- 20. Pythagorean Collections -- 21. The Seven Sages -- 22. Sextus -- 23. Shuruppak -- 24. Silvanus -- 25. Sumerian Proverb Collections -- 26. Syriac Menander -- 27. The Gospel of Thomas -- Appendix: Minor Collections -- General Bibliography.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books